Performance Based Education Funding Models for Improving the Effectiveness of Fund Management - Arthi Friedha El Famoes El Famoes; Zaenal Arifin; Sutrisno Sutrisno (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study examines the role of education financing in improving the quality of academic services in educational institutions. The problem addressed in this research is the suboptimal management and unequal distribution of education funding, which affect the effectiveness of academic services. The objective of this study is to analyze the relationship between education financing and the quality of academic services, as well as to identify key factors influencing effective financial management. This research employs a qualitative approach using a descriptive method through a literature review of relevant Indonesian journal articles and policy documents. The findings indicate that adequate and well-managed financing significantly contributes to the improvement of academic services, including facilities, teaching quality, and administrative support. Transparency and accountability in financial management also play a crucial role in enhancing institutional credibility and service effectiveness. However, disparities in funding distribution and limited managerial capacity remain significant challenges. In conclusion, effective, transparent, and equitable education financing is essential for achieving high-quality academic services, supported by strong governance and strategic financial management.